Activating the Informational Capabilities of Information Technology for Organizational Change - Leonardi, Paul M. (Organization Science, 2007)
This paper considers how the information enabled by information technology (IT) is implicated in organizational action. It begins by proposing that the relationship between technology appropriations and an organization's informal advice networks is one useful way to understand how the information that is created, modified, transmitted, and stored through the use of IT can lead to organizational change. I then present the findings of an ethnographic study of the implementation and use of a new information technology service management (ITSM) tool in a large IT organization. The findings show that a number of discrepant events led technicians to appropriate the material features of the technology in certain ways, thus providing them with new and different kinds of information than was available to them previously. Armed with such information, technicians began to seek advice differently than they had before, which led to an overall transformation in the organization's social structure. I characterize appropriations of a technology's features as a set of practices that activate the informational capabilities of a new technology through advice networks. In activating its informational capabilities, technicians transformed the potential that the technology had to create, modify, transmit, and store information in new ways into resources used to organize their work. I conclude by discussing the implications of the findings for theorizing about and management of technologically induced organizational change.